Violation of the Principle of Cooperation and Implicature in the Drama One Liter of Tears - Eko Kurniawan; Ita Fitriana; Chendy Arieshanty Paramytha Sulistyo; Anggita Stovia (Journal of Japanese Language Education and Linguistics, 2024)
The objective of this study is to provide a description of the various instances where the cooperation principle is violated and implicatures are present in the drama One Litre of Tears. The data on violation of the cooperation principle and implicatures are analyzed using Grice's theory of cooperation principle (1975) and Yule's theory of implicatures (2006). This research is a descriptive study conducted using a qualitative approach. The primary data source utilized in this study is the television drama series titled "One litre of tears." The research data consist of utterances that include breaches of the collaboration principle and encompass implicatures. Data gathering approaches employ the method of listening and recording. Data analysis techniques employ intralingual and extra-lingual correspondence methods, utilizing advanced comparison linking techniques to achieve both equalization and differentiation. The study findings indicate that there are 8 instances of violating the quantity maxim, 6 instances of violating the quality maxim, 6 instances of violating the relevance maxim, and 6 instances of violating the way maxim. These violations result in a total of 10 general conversational implicatures, 6 specialized conversational implicatures, 6 scaled implicatures, and 4 conventional implicatures.